Genome editing in cereal crops: an overview - Matres, Jerlie Mhay; Hilscher, Julia; Datta, Akash; Armario-Nájera, Victoria; Baysal, Can; He, Wenshu; Huang, Xin; Zhu, Changfu; Valizadeh-Kamran, Rana; Trijatmiko, Kurniawan R.; Capell, Teresa; Christou, Paul; et al. (Springer, 2021)
Genome-editing technologies offer unprecedented opportunities for crop improvement with superior precision and speed. This review presents an analysis of the current state of genome editing in the major cereal crops- rice, maize, wheat and barley. Genome editing has been used to achieve important agronomic and quality traits in cereals. These include adaptive traits to mitigate the effects of climate change, tolerance to biotic stresses, higher yields, more optimal plant architecture, improved grain quality and nutritional content, and safer products. Not all traits can be achieved through genome editing, and several technical and regulatory challenges need to be overcome for the technology to realize its full potential. Genome editing, however, has already revolutionized cereal crop improvement and is poised to shape future agricultural practices in conjunction with other breeding innovations.